Theater an der Wien. Théâtre sur la Vienne. - Gurk, Eduard, 1801-1841 (artist):::Creator::::::::::::; Zinke, Johann Wenzel, 1797-1858 (engraver):::Contributor::::::::::::; Mollo, Tranquillo, 1767-1837 (publisher):::Contributor:::::::::::: (Vienna; T. Mollo)
Color engraving of the Theater an der Wien in Vienna